Moina sp. Powder Supplementation as Artemia sp. Substitute Through Growth, Lysine, Histidine, Methionine, and Leucine Amino Acid Contents in Tiger Grouper x Camouflage Grouper Hybrid Larvae (Epinephelus fuscoguttatus x Epinephelus microdon) - Shobrina Silmi Qori Tartila; Shobrina Silmi Qori Tartila; Arga Iswara; Frida Choirun Nisa'; Nofita Irmayani Herlambang; Mochammad Amin Alamsjah; Agustono Agustono (Journal Omni-Akuatika, 2018)
Tiger Grouper x Cammouflage Grouper (TGCG) (Epinephelus fuscoguttatus x Epinephelus microdon) production is still low nowadays due to the insufficient price of the live feed supply during the larval phase, which is nauplii Artemia sp. One of the live feed types which is able to become a substitute of nauplii Artemia sp. is Moina sp., which has better lysine, histidine, methionine, and leucine contents, besides having the sufficient price for the supply itself. However, Moina sp. is unable to survive in the high salinity, thus it has to be produced as a powder. This condition leads to a further research whether to observe that the Moina sp. powder supplementation is able to become nauplii Artemia sp. substitute through the increased growth and the optimum better lysine, histidine, methionine, and leucine contents in TGCG larvae. The research was conducted using the complete randomized design experimental method. The result showed that Moina sp. powder is compatible as good substitute candidate of nauplii Artemia sp., as it increased the larval length growth, even it had no difference in weight growth, but it was also able to increase the larval lysine, histidine, methionine, and leucine contents.